2019
DOI: 10.18502/jovr.v14i4.5441
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ocular Surface Alterations and Concentrations of Aerial Particulate Matter

Abstract: PurposeTo evaluate ocular surface alterations in two populations at different exposure levels to particulate matter (PM) in their living and work environments.MethodsA cross-sectional study was conducted, including 78 volunteers from Argentina who lived and worked under different pollution levels in an urban (U; n = 44) or industrial zone (I; n = 34). Mean exposure level to PM was evaluated. Responses to the Ocular Symptom Disease Index and McMonnies questionnaire were obtained from all subjects. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In our study, lower TBUT, TMH and Schirmer I test values were found in the HP group, consistent with the results of previous investigations 9 , 43 . This study found that subjects in highly polluted regions have increased MG expressibility, meibum score and meiboscore, which substantiates the findings of previous epidemiologic studies 44 46 . Some studies have indicated that fine particulate air pollution might influence MG function not only by absorbing the lipid of tear film but also by entering MG, leading to lipid deficiency or maldistribution 47 , 48 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, lower TBUT, TMH and Schirmer I test values were found in the HP group, consistent with the results of previous investigations 9 , 43 . This study found that subjects in highly polluted regions have increased MG expressibility, meibum score and meiboscore, which substantiates the findings of previous epidemiologic studies 44 46 . Some studies have indicated that fine particulate air pollution might influence MG function not only by absorbing the lipid of tear film but also by entering MG, leading to lipid deficiency or maldistribution 47 , 48 .…”
Section: Discussionsupporting
confidence: 91%
“…Several epidemiological investigations have demonstrated that people with short-or long-term exposure to PM2.5 may cause dry eye, keratitis, and conjunctivitis accompanied by ocular symptoms and signs (irritation, redness, itchiness, tearing, burning, etc.) (Chang et al, 2012;Fu et al, 2017;Gutiérrez et al, 2019;Lu et al, 2019;Mo et al, 2019). It demonstrated that the possible mechanisms lie in the proinflammatory response and cytotoxicity through DNA damage and oxidative stress caused by PM2.5 exposure (Chua et al, 2019;Tang et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Very recently, there has been an upsurge of interest in the detrimental effects of PM2.5 on eyes (Chua et al, 2019;Gutiérrez et al, 2019;Yang et al, 2019). The eye is one of several organs that are constantly and directly exposed to the external environment (Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, there has been increasing interest in the harmful effect of UPM on visual systems, which is an organ directly exposed to urban air pollutants [13][14][15]. In addition, some nonclinical studies have demonstrated that exposure to UPM leads to the apoptosis and inflammation of the corneal and conjunctival epithelium in vitro and in vivo [16,17].…”
Section: Introductionmentioning
confidence: 99%